Exposure to chronic stress increases the locomotor response to cocaine and the basal levels of corticosterone in adolescent rats - Lepsch, L. B.; Gonzalo, L. A.; Magro, FJB; Delucia, R.; Scavone, C.; Planeta, Cleopatra da Silva [UNESP] (Taylor & Francis Ltd, 2005)
Repeated exposure to stress results in augmentation in the locomotor response to psychostimulant drugs. We investigated the locomotor response to a novel environment or cocaine [ 10 mg/kg, intraperitoneally (i.p.)] and basal corticosterone levels in male adolescent rats exposed to chronic restraint or variable stress. Animals in the chronic restraint group were restrained for 1 hour daily. The chronic variable stress protocol consisted of exposure to different stressors twice a day in random order. Chronic restraint and variable stress regimens began simultaneously on postnatal day (P) 25 and were applied for 10 days. During this period the control group was left undisturbed except for cleaning the cages. Three days after the last exposure to stress, cocaine- and novelty-induced locomotion were recorded in an activity cage. Plasma corticosterone levels were determined in a subset of stress and control animals. Exposure to both chronic restraint and variable stress increased cocaine- induced locomotion and basal corticosterone plasma levels, while no change was observed in the response to a novel environment. Moreover, rats exposed to variable stress displayed the greatest locomotor response following a challenge dose with cocaine when compared to control and chronic restraint stress groups. This observation indicates that the stress regimen is relevant to the degree of stress-induced sensitization to cocaine.